Efficacy of pyrantel pamoate either alone or combined with trichlorfon for control of cyathostomes of horses - Pereira, Marcelo de Campos; Del Bigio, Maurício; de Campos, Reinaldo (Brazilian Journal of Veterinary Research and Animal Science, 1994)
The anthelmintic efficacy of pyrantel pamoate, either alone or combined with trichlorfon, was evaluated for the control of strongyles of Thoroughbred horses. In all cases of positive strongyle egg counts per gram of feces (EPG) before and after treatment, pure populations of cyathostomes larvae with eight intestinal cells were consistently observed in fecal cultures. The fecal egg count reductions (FECR) were evaluated between day 7 and day 45 post-treatment. The post-treatment mean strongyle EPG counts of the horses treated with the combination of pyrantel pamoate (13.2 mg/kg) plus trichlorfon (30 mg/kg) and pyrantel pamoate alone (13.2 mg/kg) did not show significant differences (P≤0.05) during the trial, both groups reducing strongyle egg output by almost 100% on day 7, and still exhibiting an FECR of greater then 90% between day 7 and day 21. This finding indicates that both formulations are effective compounds in reducing the cyathostome fecal egg outputs in horses under field conditions.